Peripheral inflammation and AD‐related hippocampal neurodegeneration in prodromal AD patients. (1st February 2022) - Chevalier, Claire; Marizzoni, Moira; Quattrini, Giulia; Lopizzo, Nicola; Albani, Diego; Jovicich, Jorge; Cattaneo, Annamaria; Frisoni, Giovanni B
Abstract: Background: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by the presence of beta‐amyloid (Aβ42) and phosphorylated tau (P‐tau) deposits in the brain, neurodegeneration in specific brain regions, and inflammation. This study aimed at investigating the association of periferal inflammatory signaling with brain structural alterations in MCI patients with or without AD pathology. Method: Study population : 89 consecutive enrolled amnestic MCI patients. AD pathology definition : based on baseline CSF Aβ42/P‐tau level as well as APOE genotype (positivity defined as Aβ42/P‐tau ratio<7.8 for APOE4 non‐carriers, <15.2 for carriers). MRI processing : volumes of the hippocampus and its subfields were extracted with Freesurfer (version 7). Cytokine expression : pro‐ (IL6, IL8, IL1beta, TNF‐alpha, NLRP3) and anti‐ (IL10) inflammatory molecules were measured by Real Time PCR Assay. Subjects provided written informed consent, validated by the local ethics commitee Result: As expected, MCI patients with AD pathology had lower volume in the presubiculum (p=.007), subiculum (p=.030) and CA1 (p=.028) than negative patients. Moreover, positive patients showed lower expression of IL‐10 (p=.033) as well as higher expression of NLRP3 (p=.050) and IL‐8 (p=.037). Correlation analyses in all MCI patients revealed a negative association between IL10 levels and ADAScog13 (r=‐0.27, p=0.01) and P‐tau (r=‐0.22, p=0.04), and a positive association with CSF Aβ42 (r=0.22, p=0.037), hippocampal volume (r=0.23, p=0.03), temporal lobe (r=0.38, p=0.0004) and precuneus thicknesses (r=0.37 p=0.0006), consistent with a protective effect of IL10 in AD pathology. More analysis are ongoing on the effect of cytokines on different rates of atrophy of brain subfields. Conclusion: Higher expression of anti‐inflammatory factors are associated to a lower hippocampal neurodegeneration and better clinical and pathophysiological outcome in prodromal AD patients. These preliminary results suggest that non‐invasive peripheral inflammatory biomarkers could represent possible biomarkers to support the early diagnosis of AD.